Analisis Kinerja Simpang Taman Tirto Agung Semarang - Bima Dewantara; Dhony Priyo Suseno (Jurnal Teknik Sipil, 2023)
The development of transportation in the city of Semarang, especially in the Banyumanik area, has an impact on increasing the movement of people, stuff and services. this greatly encourages an increase in transportation facilities and infrastructure in the Banyumanik area. An increase in the number of vehicles that is not matched by the development of infrastructure will cause conflicts on the road, especially at intersections or roundabouts. So far, on roads in the Banyumanik area, at certain hours there is often an ineffective traffic rush with road performance being an important infrastructure in transportation. This study used calculations based on MKJI 1997. The data collection was carried out by survey directly at the intersection location in this study determined 5 days and 3 observation sessions every day. It was found that the tirto agung intersection had 322 types of intersection and the highest traffic was on Wednesday 21 June 2023 with a traffic flow value of 3528 pcu/hour, capacity 2722 pcu/hour, degree of saturation 1.296, intersection delay 92.938 sec/pcu, queue probability 69.225% - 143.302%. Based on the research results, the performance value of the Tirto Agung intersection does not meet the 1997 MKJI requirements where the degree of saturation allowed for the unsignalized intersection type is <0.75, it is necessary to have a physical intersection engineering (APILL) or non-physical (Traffic Engineering) at the intersection location.